Analisis Penerapan Metode WASPAS dan MOORA dalam Kelayakan Pengangkatan Karyawan Tetap - Kraugusteeliana Kraugusteeliana; Sitti Nur Alam; Bambang Triwahyono; Muhammad Bayu Wibisono; Fryda Fatmayati (Universitas Budi Darma, 2023)
In determining the considerations for determining employees, there are many criteria that must be owned by an employee. Each company has different criteria for determining considerations and considerations, to make employees more active and get a clear position. To determine the decisions of employees who deserve to be permanent employees, a decision support system is needed. This study aims to determine the best alternative based on predetermined criteria by applying the Multi Objective Optimization On The Basis Of Ratio Analysis (MOORA) method and the Weight Aggregated Sum Product Assessment (WASPAS) method. The research was carried out by finding the values for each attribute, then a ranking process was carried out which would determine the optimal alternative, namely determining the considerations to be carried out. As for those who are eligible to become permanent employees, alternative A6 with the acquisition value of the WASPAS method is 7.175147 and the acquisition value of the MOORA method is 0.37077. So it can be said that the methods that are suitable for application in WASPAS and MOORA are methods that are one of the appropriate methods WASPAS and MOORA are suitable methods for calculating an event.